2004
DOI: 10.4039/n03-101
|View full text |Cite
|
Sign up to set email alerts
|

Caloptilia fraxinella (Lepidoptera: Gracillariidae), a new pest of ash (Oleaceae: Fraxinus spp.) on the Canadian prairies

Abstract: In 1999, the leaf roller Caloptilia fraxinella (Ely) (Lepidoptera: Gracillariidae) was noticed for the first time in the city of Edmonton, Alberta, Canada, on ornamental green ash (Fraxinus pennsylvanica Marsh. var. subintegerrima (Vahl) Fern.) and black ash (F. nigra Marsh.) (Oleaceae). It has since been found there on Manchurian ash (F. mandshurica Rupr.) and white ash (F. americana L.). Specimens were collected and reared, and vouchers have been deposited in the Canadian Forest Service Arthropod Collection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
57
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(59 citation statements)
references
References 1 publication
2
57
0
Order By: Relevance
“…Here we tested the attractiveness and toxicity of an attracticide [G Khaskin, R Gries, G Gries, E Rosenberg, H Daroogheh & L Mircioiu 2006; novel attract and kill composition for control of pest insects; Patent Cooperation Treaty (PCT) application] against the ash leaf cone roller, Caloptilia fraxinella (Ely) (Lepidoptera: Gracillariidae), an invasive pest of horticultural ash, Fraxinus spp. (Oleaceae), on the Canadian prairies (Pohl et al, 2004). (Oleaceae), on the Canadian prairies (Pohl et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here we tested the attractiveness and toxicity of an attracticide [G Khaskin, R Gries, G Gries, E Rosenberg, H Daroogheh & L Mircioiu 2006; novel attract and kill composition for control of pest insects; Patent Cooperation Treaty (PCT) application] against the ash leaf cone roller, Caloptilia fraxinella (Ely) (Lepidoptera: Gracillariidae), an invasive pest of horticultural ash, Fraxinus spp. (Oleaceae), on the Canadian prairies (Pohl et al, 2004). (Oleaceae), on the Canadian prairies (Pohl et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Caloptilia fraxinella overwinter as adults and emerge from overwintering sites in early spring to mate and lay eggs on newly flushed ash leaflets (Pohl et al, 2004). Early instars are leaf miners and older larvae disperse to leaflets and roll leaf cones in which to pupate.…”
Section: Introductionmentioning
confidence: 99%
“…Caloptilia fraxinella (Ely) adults eclose in July when the majority of the population is in a reproductively immature state (Evenden et al, 2007), which is maintained until the following spring when adults emerge from overwintering sites to mate and lay eggs on newly flushed ash leaflets (Pohl et al, 2004). JH is important for the initiation of reproduction in female C. fraxinella in the spring (Evenden et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…All braconid parasitoid specimens reared from C. fraxinella in this study were the same species previously found to parasitise C. fraxinella in Edmonton (Pohl et al 2004). This species was identified here as A. polychrosidis Veirek (Hymenoptera: Braconidae) and was the most common parasitoid of C. fraxinella in this study (Table 1).…”
Section: Parasitoid Complexmentioning
confidence: 98%
“…The unidentified Apanteles microgastrine parasitoid was the dominant parasitoid reared from C. fraxinella in the initial seasons after its appearance in Edmonton (Pohl et al 2004) and in Saskatoon (personal observation). Other Apanteles parasitise early instars (first-third) of internally feeding Lepidoptera larvae such as Plutella xylostella (Linnaeus) (Lepidoptera: Plutellidae) (Cardona and Oatman 1975) and Phthorimae operculella (Zeller) (Lepidoptera: Gelechiidae) (Salazar and Rivera 1995).…”
Section: Introductionmentioning
confidence: 96%